2019
DOI: 10.1186/s12935-019-0845-7
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of PKM2 enhances radiosensitivity of cervical cancer cells

Abstract: Background: Pyruvate kinase isozyme type M2 (PKM2) catalyzes the final step in glycolysis and has been found to be up-regulated in multiple human malignancies. However, whether PKM2 regulates the radiosensitivity of human cervical cancer (CC) remains unknown. Methods: The expression of PKM2 in 94 patients with CC in the complete response (CR) and noncomplete response (nCR) groups, was evaluated by immunohistochemistry. The effect of PKM2 inhibition on radiosensitivity, the cell cycle, DNA damage, and apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…As regards glucose transporters, glucose transporter (GLUT) 1, GLUT3, GLUT4, and GLUT5 have been reported to induce antitumor drug resistance [39] , [40] , [41] , [42] , [43] . As to glycolytic enzymes, hexokinase (HK) [23 , [44] , [45] , [46] , 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase (PFKFB) [34 , [47] , [48] , [49] , [50] , fructose biphosphate aldolase (ALDO) [51 , 52] , glyceraldehyde 3-phosphate dehydrogenase (GAPDH) [1 , 37] , phosphoglycerate kinase (PGK) [53 , 54] , enolase (ENO) [1 , 20 , [55] , [56] , [57] , pyruvate kinase (PK) [4 , 15 , [58] , [59] , [60] , [61] , [62] , and lactate dehydrogenase (LDH) [1 , 22 , 27 , 29 , 31 , [63] , [64] , [65] , [66] , [67] , have all been shown being involved in the induction of antitumor drug resistance.…”
Section: Elements Of Glycolytic Metabolism Involved In the Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards glucose transporters, glucose transporter (GLUT) 1, GLUT3, GLUT4, and GLUT5 have been reported to induce antitumor drug resistance [39] , [40] , [41] , [42] , [43] . As to glycolytic enzymes, hexokinase (HK) [23 , [44] , [45] , [46] , 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase (PFKFB) [34 , [47] , [48] , [49] , [50] , fructose biphosphate aldolase (ALDO) [51 , 52] , glyceraldehyde 3-phosphate dehydrogenase (GAPDH) [1 , 37] , phosphoglycerate kinase (PGK) [53 , 54] , enolase (ENO) [1 , 20 , [55] , [56] , [57] , pyruvate kinase (PK) [4 , 15 , [58] , [59] , [60] , [61] , [62] , and lactate dehydrogenase (LDH) [1 , 22 , 27 , 29 , 31 , [63] , [64] , [65] , [66] , [67] , have all been shown being involved in the induction of antitumor drug resistance.…”
Section: Elements Of Glycolytic Metabolism Involved In the Inductionmentioning
confidence: 99%
“…2 ). As regards stimuli deriving from the TME, one class is represented by antitumor drugs such as chemotherapeutics [18 , 49 , 73 , 91] , TKIs [47 , 82 , 92] , or ionizing radiation [59] . In other words, the same drugs that induce tumor cell glycolysis are also victims of glycolysis-induced drug resistance.…”
Section: Stimuli Promoting Glycolysis-induced Drug Resistancementioning
confidence: 99%
“…12 Our data showed that PKM2 upregulation only partly reversed the effect of miR-1294 on DDPtreated cells, indicating that other targets of miR-1294, apart from PKM2 may contribute to miR-1294-mediated anti-tumor activity, such as IGF1R. Previous studies showed that silencing of PKM2 enhanced radiosensitivity of cervical cancer and non-small cell lung cancer, 28,39 suggesting that miR-1294/PKM2 axis may play a role in radiosensitivity of osteosarcoma.…”
Section: Dovepressmentioning
confidence: 64%
“…All experiments were performed in triplicate. The 2 -ΔΔCq method was used to calculate relative RNA expression (15)(16)(17).…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%